UPAYA MENINGKATKAN KEAKTIFAN BELAJAR MENGGUNAKAN MODEL TGT DENGAN MEDIA KACA KARTU PECAHAN PADA KELAS 4 MI DARUL ULUM - Wahab, Abdul; Agustiawan, Eko; Nuriyandini, Erika Putri; Kamila, Fathira Varach; Fadhilah, Fairuz Mariana (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to increase student learning activity in learning fractional mathematics by using the Team Games Tournament (TGT) learning model with fractional cards (KaCa). This study uses the Classroom Action Research (PTK) method with the research subject of grade IV students of MI Darul Ulum. This research consisted of two meetings with the competition, namely pre-race and post-race. In the pre-competition, the researcher conducted interviews with class teachers and showed that students' learning activity was still low, especially in fractional material mathematics lessons. In the post-competition, the researcher improved the quality of learning by improving the learning process through the TGT model in fractional materials assisted by fraction card media (KaCa). The results of the post-competition study showed that students' learning activity increased significantly in the form of becoming more active and enthusiastic in the learning process with an innovative and interactive competition game model. The results of this study can be used as a reference for teachers and researchers to improve the quality of mathematics learning in elementary schools at the same level.